New Index for Measuring Practical Knowledge Diversity: The Combination Use Diversity Index (CUDI) Applied to Cross-Cultural Ethnobotany - Yebouk, Cheikh (Ethnobotany Research and Applications, 2025)
Background: Since quantitative indices are essential for quantifying the depth of ethnobotanical knowledge, most current measures aim to account for the complexity of practical knowledge combinations by focusing on species importance or consensus. One new way to measure cultural variation in plant-use knowledge is the Combination Use Variation Index (CUDI), which is introduced in this study. Methods: CUDI is calculated by taking the number of unique “species × use” combinations a group reports and dividing it by the total number of possible combinations. Five imagined datasets for different cultural groups were created to see how the index works under different conditions of species variety, use category variety, and knowledge organization. Comparative analyses with established indices (UV, ICF, BEI, RFC, RSI) were performed. Results: CUDI values proved highly sensitive to the structure and breadth of knowledge, increasing with greater functional diversity and polyvalence in plant-use combinations, while remaining robust to differences in sample size. Comparative analysis showed that CUDI adds to traditional indices by focusing on practical usefulness instead of just how often something is cited or how much agreement there is among informants. Conclusions: When it comes to ethnobotanical research, CUDI gives researchers a transparent, robust, and easily reproducible way to quantify practical knowledge variety. Researchers can modify it for use in different fields of ethnobiology, and it addresses a methodological need in research that spans cultures and communities. Possible future uses include tracking how our understanding evolves, ranking conservation efforts, and honing quantitative ethnobotany. Keywords: CUDI, Cross-cultural comparison, Ethnobiology, Ethnobotany, Intra-group comparison, Quantitative analysis, Traditional knowledge